Enhancing Holistic Well-being of Malaysian Youth: A Financial Survival Chain Analysis - Jeffrey Lawrence D'Silva; Asnarulkhadi Abu Samah; Hayrol Azril Mohamed Shaffril; Dzuhailmi Dahalan; Nor Aini Mohamed (International Journal of Supply Chain Management, 2019)
With the advent of Industrial Revolution 4.0 and technology development, community well-being is given more attention so that mankind will be able to achieve soundness in living. The aim of this paper is to depict the holistic well-being of Malaysian youth particularly in the area of finance since many youths face daunting challenges due to problems associated with money. This is a quantitative study involving 200 working youths between the age group of 24-30 years. In terms of objective well-being, the study revealed that Malaysian youth are prudent and wise with their money management. On the other hand, the subjective well-being showed that the youth are facing financial constraints for the purpose of investment, holidaying and to purchase medical insurance. The study recommends that the financial survival chain of working youth could be boosted if the concerned parties paid more attention to easing youth involvement in investing in safe investment portfolios as well as providing them with affordable holiday and medical insurance packages.